Cybersecurity - A Self-Teaching Introduction - Goyal, K. K; Garg, Amit (Mercury Learning and Information, 2020)
This book is designed to provide the reader with the fundamental concepts of cybersecurity and cybercrime in an easy to understand, self-teaching format. It introduces all of the major subjects related to cybersecurity, including data security, threats and viruses, malicious software, firewalls and VPNs, security architecture and design, security policies, Cyberlaw, and more. Features: Provides an overview of cybersecurity and cybercrime subjects in an easy to understand, self-teaching format; Includes discussion of information systems, cryptography, data and network security, threats and viruses, electronic payment systems, malicious software, firewalls and VPNs, security architecture and design, security policies, cyberlaw, and more.